Por falar em culturas... : histórias que marcam a cidade - Uberlândia-MG - Freitas, Sheille Soares de (2009)
This work insists in the reflection on questions of the to live and to produce the city of Uberlândia. I tried to put in focus propositions and transformations that appears in the end of the century XX and beginning of the century XXI, realizing that their residents' marks continue to undertake disputes in the city. In that sense, the interest was explained unequal territories and in constant elaboration and tension. I felt the need to criticize the simple plural enumeration of practices produced in the social relationships, I sought explained change processes in the people's life that appeared synthesized in certain notions of difference, revitalization, preservation, cultural patrimony and urban space. The expectation was to problematize those explanatory notions, intending to evidence divided experiences and unequal. To work with the histories that are produced by certain residents in the making of the city brought new social maps, territories produced by the relationships that built. When problematizing the relationships lived in the city demanded to expand perspectives on that place. I suggested, therefore, to move in a resignation proposed recurrent and to see as the dynamics of living if does in the confluence with a wide field of limits and pressures. I appeared as the social practices maintained in to live, to work, to maintain and to explain values are produced and tensioned certain manners of living, looking for to see that dynamics in a same historical process. My intention was to notice as the process of construction of the patrimonies and territories of the city is executed in her existence. For that, I chose some roads of that construction as points of my investigation and I intended to share, with other residents, my research intentions, for like this to produce histories of that city, with the manners of to live and to struggle for her. To leave the motion that there are a history and a place to locate her, it pointed treading the city realizing and printing rhythms, habits, custom, in a polyphony of interests and expectations, working with the class pressures that foment that composition of territories and transformations. In the impermanent of what proposed, leaning that the relevance of my text is in the course of yours to do and in the argues and practices that it can urge from now on. The attempt was to put to the test that, in the moment, it foments my political practice.